Exploring the effects of health behaviors and mental health on students' academic achievement: a cross-sectional study on lebanese university students - Dalal Hammoudi Halat; Souheil Hallit; Samar Younes; Mira AlFikany; Sanaa Khaled; Maha Krayem; Sami El Khatib; Mohamad Rahal (BMC, 2023)
Abstract Background High academic achievement, an important determinant of future success, is known to be influenced by many factors including dietary behavior, lifestyle and mental health, among others. The objectives of the current study were to explore university students' nutritive habits, daily lifestyle, and mental status, and to scrutinize the associations between these factors and students' academic achievement. Methods A cross-sectional study was conducted among students of a private Lebanese university, using an electronic survey. Diet, eating habits, physical activity, sleep, and smoking were evaluated, and mental health was assessed using a validated Arabic version of the combined Depression, Anxiety, Stress Score (DASS-8). Academic achievement was measured using the Subjective Academic Achievement Scale (SAAS). Results A total of 1677 students participated in the questionnaire. The results of a linear regression taking the SAAS score as the dependent variable, showed that students who have a non-scientific versus scientific major (Beta = 0.53), and having breakfast ≥ 4 days per week compared to less than 2 days (Beta = 0.28) were significantly associated with higher SAAS scores. More psychological distress (Beta = − 0.06) and a higher number of days of eating out (Beta = − 0.07) were significantly associated with lower SAAS scores. Conclusions This is the first investigation on a Lebanese university students' academic success in relation to lifestyle and mental profiles. Better academic achievement was demonstrated by students having healthier dietary and lifestyle habits, as well as less distressing mental status. Such results, in light of the compounded and unprecedented crises with which Lebanon has been assailed, suggest the need to focus on promoting healthy habits among students in higher education as a possible driver of better academic success.